a]
C = (-1, -5) i D = (3, 3)
{-a + b = -5 / * (-1)
{3a + b = 3
{a - b = 5
+ {3a + b = 3
--------------------
4a = 8 / : 4
a = 2
-2 + b = -5
b = -5 + 2
b = -3
y = 2x - 3
b]
C = (-2, 4) i D = (8, -1)
{-2a + b = 4
{8a + b = -1 / * (-1)
{-2a + b = 4
+ {-8a - b = 1
--------------------
-10a = 5 / : (-10)
a = -0,5
-2 * (-0,5) + b = 4
1 + b = 4
b = 4 - 1
b = 3
y = -0,5x + 3
c]
C = (-3, -3) i D = (6, 3)
{-3a + b = -3 / * (-1)
{6a + b = 3
{3a - b = 3
+ {6a + b = 3
--------------------
9a = 6 / : 9
a = 6/9 = 2/3
-3 * 2/3 + b = -3
-2 + b = -3
b = -3 + 2
b = -1
y = 2/3x - 1